녹내장성 시신경유두함몰 지표로서의 기울기 - 안상일; Sang Il Ahn; 장지호; Jee Ho Chang (Daihan angwa haghoi jabji, 2013)
목적: 빛간섭단층촬영기를 이용하여 시신경유두함몰의 기울기를 수치화하고, 이 기울기가 함몰의 정도를 반영하며 정상군과 녹내장군에서 차이가 있음을 보고자 한다. 대상과 방법: 정상 40안, 녹내장 39안을 대상으로 험프리 자동시야검사계를 이용한 시야검사를 하고 Cirrus 스펙트럼 영역 빛간섭단층 촬영기로 시신경유두를 검사하였다. 본 연구를 위해 제작한 프로그램을 이용하여 OCT 데이터를 3차원 표면 지도로 재구성한 후 기울기 지표들을 비교 분석하였다. 결과: ``기울기합``, ``역치이상 기울기합``, ``역치이상 기울기합 / 면적``은 녹내장군이 정상군보다 통계적으로 유의하게 컸으며(p＜0.05), 이들 기울기 지표들의 AUROC는 0.718에서 0.753 범위였다. 이중 ``역치이상 기울기합 / 면적``은 시야검사의 Mean deviation 값과 통계적으로 유의한 상관관계를 나타내었다(r=-0.250, p=0.028). 결론: 빛간섭단층촬영기로 구한 시신경유두함몰 기울기는 녹내장성 유두 함몰의 유용한 임상지표가 될 수 있을 것이다. <대한안과학회지 2013;54(3):462-468> Purpose: To objectively define the degree of cupping, the authors extracted 3-dimensional slope surface maps from Cirrus HDTM-OCT data and assessed their differentiating characteristics between normal subjects and glaucomatous patients. Methods: One eye from each of 40 normal subjects and 1 eye from each of 39 patients with glaucoma were examined using automated visual field perimetry and Cirrus HDTM-OCT. The Optic Disc Cube 200 × 200 protocol was performed. The individual OCT data were reconstructed as the 3-dimensional surface maps of the optic disc cup and the slope of each contour was calculated using custom-developed software. Several disc cup slope parameters were derived. The parameters measuring the internal features of the optic disc cup were calculated and compared between groups. Results: Sum of cup slope, sum of thresholded cup slope, and sum of thresholded cup slope / thresholded cup area parameters were differentiating factors between the normal and glaucoma groups (p < 0.05). The area under the receiver operating characteristic curve (AUROC) value of the slope parameters ranged from 0.718 to 0.753. The sum of thresholded cup slope / thresholded cup area parameter was well correlated with visual field mean deviation (r = -0.250, p = 0.028). Conclusions: The optic disc cup slope parameter obtained with OCT may be a useful parameter for representing glaucomatous cupping. J Korean Ophthalmol Soc 2013;54(3):462-468